A comprehensive mathematical model of drug release kinetics from nano-liposomes, derived from optimization studies of cationic PEGylated liposomal doxorubicin formulations for drug-gene delivery. (2nd January 2018) - Haghiralsadat, Fateme; Amoabediny, Ghasem; Helder, Marco N.; Naderinezhad, Samira; Sheikhha, Mohammad Hasan; Forouzanfar, Tymour; Zandieh-doulabi, Behrouz
Abstract: This study focuses on the development of a universal mathematical model for drug release kinetics from liposomes to allow in silico prediction of optimal conditions for fine-tuned controlled drug release. As a prelude for combined siRNA-drug delivery, nanoliposome formulations were optimized using various mole percentages of a cationic lipid (1, 2-dioleoyl-3-trimethylammonium-propane, DOTAP) in the presence or absence of 3 mol% distearoyl phosphoethanolamine, polyethylene glycol (PEG–2000mDSPE). Outcome parameters were particle size, zeta potential, entrapment efficiency, in vitro drug release, and tumor cell kill efficiency. The optimized formula (containing 20% DOTAP with 3% DSPE-mPEG(2000) was found to be stable for six months, with round-shaped particles without aggregate formation, an average diameter of 71 nm, a suitable positive charge, and 89% drug encapsulation efficiency (EE). The 41% drug release during 6 h confirmed controlled release. Furthermore, the release profiles as functions of pH and temperature were investigated and the kinetics of the drug release could adequately be fitted to Korsmeyer–Peppas' model by multiple regression analysis. The statistical parameters confirmed good conformity of final models. Functionality of the novel cationic liposome formulations (± DOX) was tested on osteosarcoma (OS) cell lines. Increased OS cell toxicity (1.3-fold) was observed by the DOX-loaded vs. the free DOX. A feasibility pilot showed that siRNA could be loaded efficiently as well. In conclusion, we have established a predictive mathematical model for the fine-tuning of controlled drug release from liposomal formulations, while creating functional drug-delivery liposomes with potential for siRNA co-delivery to increase specificity and efficacy. Graphical Abstract: